L’agence de presse Reuters : l’information comme levier d’influence britannique en Asie du Sud-Est, XIXe – XXe siècles - Cathy Monarque (Revue Française de Civilisation Britannique)
The reinvestment of Southeast Asia at the turn of the 21st century is an issue that the United Kingdom has not failed to address in order to maintain its position on the world stage. Whether strategic, diplomatic or economic, British objectives have intrinsically been linked to a quest for influence in this region since the eve of independence. As a channel for and actor of international cultural relations, information is a lever of influence on which press agencies, such as Reuters, rely to participate in the circulation of representations and in the cultural projection of Britain.